Scars of a Colonial History: White Privilege, Race Relations and Anti-Apartheid Sensibilities in Athol Fugard’s “Master Harold”... and the Boys - Burr, Marshall (Pivot: A Journal of Interdisciplinary Studies and Thought, 2023)
Central to virtually any indictment of South African literature, its historiography, or otherwise culturally and politically influenced modes of representation persist themes of social, political, and racial inequality. That is not to say that all South African cultural productions revolve around a centrifuge of racially focused social commentary; rather, that when historicizing a work of South African aesthetics such themes inevitably arise because of the nation’s colonial history and the Eurocentrism that have pervaded its modern socio-political foundations. When examining South African aesthetic/cultural representations (in this case, a literary text) it is thus crucial to properly locate the work in as full a historical context as possible. My research therefore aims to link South Africa’s history of colonization with the damaged race relations that ensued in the twentieth century as represented in a prominent work of South African theater: Athol Fugard’s “Master Harold” … And the Boys. My essay traverses the history of British and Dutch colonization in South Africa and seeks therein to register foundations for the Eurocentric, whitewashed ideologies which would eventually translate into official state policy in 1948 and which precipitated the broken race relations that Fugard’s semi-autobiographical play interrogates. I discuss Fugard’s depiction of white privilege while systematically linking such representations back to their colonial foundations, and ultimately assess Fugard’s play as a condemnation of white supremacy and as a plea for the recalibration of prejudiced racial hierarchies.